The effects of lian gong in hypertensives attended a family healthcare unit in the city of Parnaíba, Piauí - Elce de Seixas Nascimento; Maria Poliana Ferreira Castelo Branco; Ana Karine de Figueiredo Moreira; Fuad Ahmad Hazime (Universidade de Fortaleza, 2012)
Objective: To understand the effects of Lian Gong in hypertensive users of Family Health Unity. Methods: A descriptive qualitative study, involving 20 volunteers, regardless of gender, aged 45 to 70 years residing in the city of Parnaíba-PI, Brazil. The intervention was performed in quiet and noise-free environment, from August to September 2011, three times per week, with a total of 30 sessions. We used the tool Focus Group at the beginning and end of the intervention. We applied the technique of thematic analysis of the Collective Subject Discourse (CSD) using three methodological approaches: main idea, key expressions and CSD. Basic statistics operations were used (percentages) to quantify the lines. Results: Before the intervention, the group reported having hypertension perceived by the manifestation of physical symptoms and / or psychic symptoms based on the diagnosis and treatment rejection, revealing a superficial level of knowledge or misinformation about the disease. After the intervention, improvement in physical and emotional symptoms, social relationships and family was reported, as well as the difficulty of changing habits, which can be alleviated with the interdisciplinary support and continuation of exercise. Final Thoughts: The practice of Lian Gong was effective for improving the physical and emotional state of hypertensive patients and may be an adjuvant therapy to control hypertension in primary health care.